Pendevelopment and legal protection for UMKM for improvement Tocommunity welfare - Dwita rahmawati; Hardian iskandar (Jurnal Justiciabelen, 2022)
Mmicro, small and medium enterprises have a strategic role in strengthening the people's economy nationally. The government needs to pay more attention to strategies and policies for empowering UMKM. This paper discusses the problems related to the development of UMKM that aim to improve welfare for the community and forms of protection for UMKM. This study uses a normative-juridical method with an analytical-descriptive approach. The results of the study show that problems related to the development of UMKM consist of several things, including marketing difficulties, financial limitations, limited human resources, problems with raw materials, and limited knowledge of modern technology. Until now, the form of legal protection for UMKM that the government has provided has only been through the simplicity of the requirements and procedures for applying for business licenses, the development procedures, and the procedures for providing administrative witnesses and controlling the empowerment of UMKM. The government needs to provide assistance to business actors who need counseling and legal assistance. The government should also be able to maintain a balanced market price, and there should be strict sanctions for business actors who monopolize prices. The central government has taken steps to make efforts to provide welfare for UMKM in terms of being provided with ease in dealing with administrative documents as well as the existence of more specific legal protection, which is realized by the existence of the Job Creation Law,